Comparative Analysis of the Battery Charging System using Digital and PI Controller - Mohd Razali, Danial Hakim; Abu Bakar, Afarulrazi (Evolution in Electrical and Electronic Engineering, 2021)
Lithium-ion batteries are growing in popularity due to increasing demand and higher energy density; majorly contributed by the ever-advancing technology of portable devices and electric vehicles. A battery charger, or voltage regulator, which is crucial for charging and discharging, therefore must be specifically designed to prevent damages. This study is concerned with designing a digitally controlled charging system using a DC-DC boost converter, which is able to operate with a wide range of input voltage with specific output voltage. All the critical parameters for the proposed design components based on 100kHz switching frequency had been calculated and modeled using MATLAB/Simulink software. Several PI parameters had also been applied in order to verify the effectiveness of the model. The PI controller was simulated with different Kp and Ki, and the results had been analyzed in detail. The digital controller was programmed using Field Programmable Logic Array using Quartus II software. The results showed that with Kp =0.0009 and Ki =11.4 gave better performance than other parameters, with a rise time of 200.45μs, overshoot -1.503%, settling time of 10.40ms with an output voltage ripple less than 1%. Finally, A digital controller, Altera DE2-70 board with parallel 8-bit ADC, had been used to verify the performance of the proposed digital controller.